Resource Estimations in Contingency Planning for Foot-and-Mouth Disease - Boklund, Anette; Mortensen, Sten; Johansen, Maren H.; Halasa, Tariq (Frontiers in Veterinary Science, 2017)
Preparedness planning for a veterinary crisis is important to be fast and effective in the eradication of disease. For countries with a large export of animals and animal products, each extra day in an epidemic will cost millions of euros due to the closure of export markets. This is important for the Danish swine industry, which had an export of €4.4 billion in 2012. The purposes of this project were to: 1) estimate the resources needed during an outbreak of foot and mouth disease (FMD) in Denmark, 2) identify areas, which can delay the control of the disease, and 3) develop an iterative tool, which can easily be updated, when knowledge is gained from other veterinary crises or during an outbreak of FMD. The stochastic simulation model DTU-DADS was used to simulate spread of FMD in Denmark. For each task occurring during an epidemic of FMD, the time and personnel needed per herd was estimated by a working group with expertise in contingency and crisis management. By combining this information, an iterative model was created to calculate the needed personnel on a daily basis during the epidemic. The needed personnel was predicted to peak within the first week with a requirement of approximately 123 (65-175) veterinarians, 33 (23-64) technicians and 36 (26-49) administrative staff on day 2, while the personnel needed in the Danish Emergency Management Agency (responsible for the hygiene barrier and initial cleaning and disinfection of the farm) was predicted to be 174 (58-464), mostly recruits. The time needed for surveillance visits was predicted to be the most influential factor in the calculations. Based on results from a stochastic simulation model, it was possible to create an iterative model to estimate the requirements for personnel and materiel during an FMD outbreak in Denmark. The model can easily be adjusted, when new information on resources appears from management of other crisis or from new model runs.